Clinical and cardiac characteristics of primary bilateral macronodular adrenal hyperplasia: Characteristics of bilateral adrenal hyperplasia - Miao, Sisi; Lu, Lin; Si, Shengyong; Peng, Dandan; Zhong, Ya; Li, Zhijing; Yu, Zhenqiu (Journal of Medical Biochemistry, 2023)
Background: Cardiovascular disease is the leading cause of death from Cushing’s syndrome (CS). Primary bilateral macronodular adrenal hyperplasia (PBMAH), a rare cause of CS, is clinically distinct from the other common types of CS, but its cardiac characteristics have been poorly studied.Methods: The clinical data, steroid hormones and echocardiographic variables were collected in 17 PBMAH patients. Twenty-one CS patients with cortisol-producing adenoma (CPA) were collected as controls.Results: In the PBMAH group, the proportion of female was lower (35.30 vs 100.00%), the age was older (55.76 ± 2.42 years vs 39.57 ± 2.72 years), and the course of disease was longer [13.00 (5.00, 21.50) years vs 1.58 (1.00, 5.00) years]. The proportion of PBMAH patients with hypertension was higher than that of CPA patients (100.00% vs 61.90%). Plasma cortisol and 24h urinary free cortisol (24h UFC) were lower in PBMAH patients than that in CPA patients [morning cortisol 19.50 (15.35, 24.48) μg/dl vs 28.30 (22.88, 29.89) μg/dl, 24h UFC 106.20 (65.35, 156.58) vs 506.23 (292.53, 712.18) μg]. The PBMAH group had longer right ventricular diameter (24.06 ± 1.23 mm vs 20.48 ± 0.83 mm), left atrial diameter (39.41 ± 1.15 mm vs 32.86 ± 0.76 mm), and a higher rate of diastolic dysfunction (76.50% vs 38.10%) than the CPA group. Univariate regression analysis showed that combination of hypertension and duration of hypertension had significant effects on left atrial diameter (b=6.383, P=0.001; b = 0.276, P
Keywords: Primary bilateral macronodular adrenal hyperplasia; PBMAH; Cardiac; Echocardiogram; Steroid hormone